The effects of speed and performance level on race walking kinematics - Pavei, G.; La Torre, A. (Sport Sciences for Health, 2016)
Purpose: Race walking is a very technical discipline of athletics, which is regulated by two peculiar constraints: straighten knee from heel strike to midstance and flight phase absence while race-walking. For this reason, several studies addressed technical factors as determinant of athletes` performance. The aim of this study was to analyse differences in technique across athletes` levels (regional—national—international), and describe race walking kinematics at increasing speeds. Methods: Fifteen athletes race-walked for 1 min on a treadmill at increasing speeds (from 2.78 m s-1 to exhaustion). Three-dimensional kinematics data were recorded through a motion capture system sampling at 300 Hz. Results: Step length, step frequency and flight time increased linearly with speed, but step length was the major determinant to raise speed. At increasing speeds, joints angles curves reported a backward time shift (e.g., anticipation of the movement), without altering joints range of motion, a further evidence of the rules influence on athletes` technique. Among athletes` levels the only difference found regarded the maximal race walking speed: international 4.97 ± 0.25 m s-1, national 4.61 ± 0.14 m s-1 and regional 4.22 ± 0.14 m s-1. Conclusion: Athletes` angular kinematics did not change increasing race-walking speed and did not show differences among athletes` performance level. Further studies with combined metabolic and electromyography analyses are needed to better elucidate performance determinants and discriminate athletes` level. ABSTRACT FROM AUTHOR